Thermal-tolerant potential of ordinary Chlorella pyrenoidosa and the promotion of cell harvesting by heterotrophic cultivation at high temperature - Dai, Yu-Ren; Wang, Die; Zhu, Yu-Rong; Yang, Kun-Xiao; Jiao, Ning; Sun, Zhong-Liang; Wang, Shi-Kai (Frontiers in Bioengineering and Biotechnology, 2022)
During the heterotrophic cultivation of microalgae, a cooled process against temperature rise caused by the metabolism of exogenous organic carbon sources greatly increases cultivation cost. Furthermore, microalgae harvesting is also a cost-consuming process. Cell harvesting efficiency is closely related to the characteristics of the algal cells. It may be possible to change cell characteristics through controlling culture conditions to make harvesting easier. In this study, the mesophilic Chlorella pyrenoidosa was found to be a thermal-tolerant species in the heterotrophic mode. The cells could maintain their maximal specific growth rate at 40°C and reached 1.45 day−1, which is equivalent to that of cultures at 35°C but significantly higher than those cultured at lower temperatures. Interestingly, the cells cultured at 40°C were much easier to be harvested than those at lower temperatures. The harvesting efficiency of the cells cultured at 40°C reached 96.83% after sedimentation for 240 min, while the cells cultured at lower temperatures were reluctant to settle. Likely, the same circumstance occurred when cells were harvested by centrifugation or flocculation. The promotion of cell harvesting for cells cultured at high temperatures was mainly attributed to increased cell size and decreased cell surface charge. To the best of our knowledge, this is the first report that cells cultured at high temperatures can promote microalgae harvesting. This study explores a new approach to simplify the cultivation and harvesting of microalgae, which effectively reduces the microalgae production cost.